Exact solutions of space–time fractional KdV–MKdV equation and Konopelchenko–Dubrovsky equation - Tang Bo; Tao Jiajia; Chen Shijun; Qu Junfeng; Wang Qian; Ding Ling (Open Physics, 2020)
In the present study, we deal with the space–time fractional KdV–MKdV equation and the space–time fractional Konopelchenko–Dubrovsky equation in the sense of the conformable fractional derivative. By means of the extend (G′G)\left(\tfrac{G^{′} }{G}\right)-expansion method, many exact solutions are obtained, which include hyperbolic function solutions, trigonometric function solutions and rational solutions. The results show that the extend (G′G)\left(\tfrac{G^{′} }{G}\right)-expansion method is an efficient technique for solving nonlinear fractional partial equations. We also provide some graphical representations to demonstrate the physical features of the obtained solutions.